RESPONSE SURFACE METHODOLOGY FOR OPTIMIZING THE MARINATION CONDITIONS DURING THE PROCESSING OF RAINBOW TROUT FILLETS - a Ö. P. Can; M. Ersan (Journal of Animal and Plant Sciences, 2013)
The objective of this study was to determine using response surface method the optimum points of the rosemary essence oil concentration along with the actual marination time in terms of colour criteria for rainbow trout fillets marinated by the addition of differing rates of rosemary essence oil. The study was conducted in three stages (first satage: 9 different experimental groups depending on the amount of rosemary oil (0.5%, 1% and 1.5%) and actual marination time (6, 12 and 24 hours), second stage: modelling was conducted with RSM and third stage: the optimum point for the model). The experimental groups of first and second stage were examined organoleptic (view, texture, colour, odor, total assessment (TA) and colour analysis (L* , a* and b* values) were conducted. The samples of third stage were analyzed in terms of microbiological (total mesophile aerobe bacteria (TMAB), psycrophile bacteria (PB), lactic acid bacteria (LAB), Enterobacteria (EB), yeast and mould (YM)), chemical (pH total volatile basic nitrogen value (TVB-N) and thiobarbituric acid number (TBA)), organoleptic (view, texture, colour, odor, total assesment) and colour criteria (L* , a* and b* values). Rosemary oil amount and actual marination time (second stage sample) determined by the design were found as 0.8% and 19 hours, respectively. L* , a* and b* values determined at this point were determined as 51.1, 1.79 and 8.03 respectively. Total mezophile aerobe bacteria count reached 7.9 log10 cfu/g in group B (third stage sample) on 98th day
Keywords: Response surface methodology; fish fillet; rosemary oil; shelf life